Industry Recommendations: Characteristics, Investment Value, and Relation to Firm Recommendations - Kadan, Ohad (Institutional Knowledge at Singapore Management University, 2010)
We study analysts’ industry recommendations. We find that the distribution of industry recommendations is quite balanced. Analysts show more optimism towards industries with high levels of R&D, past profitability and past returns. Industry recommendations possess investment value as portfolios based on these recommendations generate risk-adjusted abnormal returns. Finally, industry recommendations contain information which is orthogonal to that included in firm recommendations, and more so for brokers who benchmark their firm recommendations to industry peers. Consequently, the investment value of analysts’ recommendations is enhanced when both industry and firm recommendations are used.